Preventing conflict upstream: impunity and illicit governance across Colombia's borders. Issue 1 (2nd January 2018) - Idler, Annette
Abstract: This article explores how transnational borderlands matter for conflict prevention and, in particular, so-called upstream engagement, which aims to reduce threats to global stability and security that arise from the world's increasing interconnectedness. Accounting for transnational borderlands in vulnerable regions is crucial for conflict prevention as pursued by the defence and security sector because borderlands are catalysts of the negative side of global interconnectedness: they are business hubs for transnational organised crime, sites of retreat for conflict actors, and safe havens for terrorists. The border areas' proneness to impunity and the ability of violent non-state actors to govern these spaces illicitly contribute to the emergence of these characteristics. I therefore argue that upstream conflict prevention needs to do two things to address these risks: first, to overcome a national security approach centred on the borderline and instead acknowledge transnational security dynamics in borderlands on both sides of the border; second, to overcome the state-centred governance lens to also consider governance exerted by non-state actors. The article draws on empirical data from a six-year study including over a year of fieldwork in and on Colombia's borderlands.